2021
DOI: 10.3390/cancers13061289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pancreatic Resection on Survival in Locally Advanced Resectable Gastric Cancer

Abstract: Whether gastric adenocarcinoma (GC) patients with adjacent organ invasion (T4b) benefit from aggressive surgery involving pancreatic resection (PR) remains unclear. This study aimed to clarify the impact of PR on survival in patients with locally advanced resectable GC. Between 1995 and 2017, patients with locally advanced GC undergoing radical-intent gastrectomy with and without PR were enrolled and stratified into four groups: group 1 (G1), pT4b without pancreatic resection (PR); group 2 (G2), pT4b with PR; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the present study, the 5-year OS rate of pT4b GC patients who received MVR surgery was 39.1%, which was a little higher than the previous results. This may be related to the fact that the previous results have illustrated that prognosis in the patients combined with pancreas resection, especially in patients who underwent pancreaticoduodenectomy, was poor than patients combined other organs resection during MVR surgery 3 , 10 , 11 . In a Korea retrospective study, the 5-year OS rates of pT4b patients combined pancreas resection group and combined other organs resection were 23.3% and 42.1% ( P =0.002), while in the pancreaticoduodenectomy group, the 5-year OS rates was 0% 11 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the present study, the 5-year OS rate of pT4b GC patients who received MVR surgery was 39.1%, which was a little higher than the previous results. This may be related to the fact that the previous results have illustrated that prognosis in the patients combined with pancreas resection, especially in patients who underwent pancreaticoduodenectomy, was poor than patients combined other organs resection during MVR surgery 3 , 10 , 11 . In a Korea retrospective study, the 5-year OS rates of pT4b patients combined pancreas resection group and combined other organs resection were 23.3% and 42.1% ( P =0.002), while in the pancreaticoduodenectomy group, the 5-year OS rates was 0% 11 .…”
Section: Discussionmentioning
confidence: 95%
“…Although Tran et al found that MVR surgery with pancreas resection was not associated with an increased frequency of postoperative complications and mortality 10 . The gastrectomy combined with pancreaticoduodenectomy was considered to have high risk of postoperative death and complications 3 , 10 . Thirdly, the number of cases in the present study and previous studies were relatively small, which could potentially bias the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data also showed that in-front surgery alone had significantly higher rates of mortality/complications and shorter OS time than conversion surgery or in-front surgery plus PCT, indicating that systemic treatment is the standard of care for mGC. Postoperative complications are independent risk factors for the early recurrence of GC after curative resection, which is related to the inflammatory cytokine cascade-induced dysfunction of immune cells, including cytotoxic T-lymphocytes, natural killer cells, and antigen-presenting cells, and a delay in the initiation of postoperative chemotherapy [30][31][32]. Postoperative complications and surgery-related immune suppression are major concerns in in-front surgery for mGC.…”
Section: Discussionmentioning
confidence: 99%